Cement Production and Sustainable Rural Farming Livelihood in Nigeria: Striking a Sensible Balance Through Environmental Legislation and Enforcement - Okojie, Luke O. (European Journal of Sustainable Development, 2014)
This paper undertook the damage valuation of cement production induced air pollution on rural farming livelihood, assessed the impact on farmers’ profitability as well as investigating the corporate social responsibility investment of the cement companies in the producing host communities in Nigeria. It then examined how legislation and enforcement can be made to strike a sensible balance between the environmental damage enabled by cement pollution and ensuring a sustainable farming livelihood. A two stage simple random sampling procedure was adopted for the paper to select a total of 120 respondents in the target and control areas. Data were analyzed using descriptive statistics, Dichotomous–Choice Contingent Valuation Method (DC- CVM) that terminated into the logit model and the budgetary analysis. The total Willingness-To-Pay (WTP)/annum to avert the negative externalities on the host communities’ farming livelihood was N3.21 billion. The profitability in farming in the target cement producing area with respect to the net farm income and the rate of return to capital investment were lower in the target as compared to the control area. The Corporate Social Responsibility (CSR) investments of the cement producing companies were small compared to the profits realized by them. The proportions of the CSR investments with respect to the company’s profits were between 0.4% and 1.6% for the five years considered in the paper. Efforts have been made by the government to enact laws, regulations and standards to ensure environmentally sound and sustainable environment though the institution initially put in place to implement them was not given legal powers of enforcement. Things are however changing with the establishment of another with such powers. It is only by such proper implementation, a sensible balance can be struck between uncontrolled cement dust pollution associated with excess profits to the cement producers and sustainable farming livelihood guarantee with enhanced corporate social responsibility ensured to the host communities. Keywords: Environmental damage, pollution, valuation, corporate social responsibility, livelihood, legislation, enforcement.